2011
DOI: 10.1155/2011/848467
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Geomagnetic Variations Possibly Linked with the Taiwan Earthquake (Mw=6.4) on 19 December 2009

Abstract: On 19 December 2009, the eastern part of Taiwan at approximate depth of 45 km was struck by a strong earthquake (Mw = 6.4). The epicenter was located about 20 km away from the Hualien (HLN) station in Taiwan. By analyzing data from the HLN station and Amami Oshima (AMA) in Japan as a remote reference, the geomagnetic east-west (D) and vertical (Z) components recorded at the HLN station are showing no correlation with those at the AMA station in December 2009. Anomalous variations of ∼10-15 nT started about one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…In an investigation of geomagnetic eld in ULF range (Pc3-5) from 14 stations of Canadian array reported signi cant enhancement in spectral ratio (Currie and Waters, 2014). In Sumatra region, the anomalous uctuations observed in H led in Pc3 range two weeks prior to occurrences of earthquake (Takla et al, 2011). In the same study area, the anomalous signature also reported in polarization ratio (Z/H) at frequency 0.06 Hz (Ahadi et al, 2015).…”
Section: Discussionsupporting
confidence: 60%
“…In an investigation of geomagnetic eld in ULF range (Pc3-5) from 14 stations of Canadian array reported signi cant enhancement in spectral ratio (Currie and Waters, 2014). In Sumatra region, the anomalous uctuations observed in H led in Pc3 range two weeks prior to occurrences of earthquake (Takla et al, 2011). In the same study area, the anomalous signature also reported in polarization ratio (Z/H) at frequency 0.06 Hz (Ahadi et al, 2015).…”
Section: Discussionsupporting
confidence: 60%
“…The studies that the authors have realized within this new scientific context (as well as technological) have allowed us to understand that there are actually two families of pre-seismic radio emissions: 1) radio emissions identified as Earth's geomagnetic field disturbances related to "near Earth" solar wind proton density increase variations, and for this reason it can be seen from any point on the Earth (this is "no-local" type emissions); 2) radio signals are not connected directly to the solar and geomagnetic activity: these radio signals are probably generated by piezoelectricity phenomena occurring near the focal area of the earthquake and are detectable near earthquake epicenter (this is a "local" type emissions). It is therefore clear that the monitoring of solar activity and Earth's geomagnetic activity is an activity of fundamental importance to be able to have a general understanding of pre-seismic radio signals nature [29]; [30]; [31]. In fact, as the authors demonstrated that all M6+ earthquakes that occur on a global scale are always preceded by an increase of the solar wind proton density near Earth, the solar and geomagnetic activity monitoring is a seismic prediction method that has proven reliable for understanding when we can expect a recovery of the M6+ global seismic and could be used internationally as an indicator of seismic risk in the countries where there are potentially destructive earthquakes and tsunamis.…”
Section: Resultsmentioning
confidence: 99%
“…The authors in [27] proposed that certain magnetic anomalies may arise from partially serpentinized ultramafic bodies, which contain metal alloys as the source material for magnetism, exhibiting a Curie temperature ranging from 620 • C to 1100 • C. By utilizing P-wave tomography, the authors in [29] developed a temperature model beneath the SE-Carpathians, identifying a hotter region west of the Vrancea slab starting at a depth of 75 km. Some authors have interpreted geomagnetic anomalies as a result of stress accumulation, which leads to an enhancement of the conductivity structure of the lithosphere [30,31]. Additionally, it must be noted that geomagnetic anomalies can be generated by anthropogenic activities or thermal variations that affect the instrument.…”
Section: Exploring the Link Between B Y Variance And Total Seismic En...mentioning
confidence: 99%